Macromoléculas derivadas do cardanol hidrogenado: síntese e propriedades líquido cristalinas - Mota, João Paulo Ferreira (2016)
In this study were obtained some macromolecules, new asymmetric meso-porphyrins and phthalocyanines, derived from hydrogenated cardanol, the majority constituent of the cashew nut shell liquid (technical CNSL). Where, in addition, it was evaluated the liquid crystalline properties of these compounds in heating and cooling cycles. The data obtained by spectroscopic and spectrometric methods, 1H and 13C NMR, UV-vis, MS (MALDI-TOF) and IR have indicated the efficiency of the synthetic procedure, that allowed us, to obtain the new meso-5-mono-4-hydroxyphenyl-10,15,20-tri-4-[2-(3-pentadecylphenoxy)ethoxy]phenyl porphyrin free and metalated with nickel, cobalt, copper and zinc, as well as the 2(3),9(10),16(17),23(24)-tetrakis(-3-pentadecylphenoxy) phthalocyanine free and metallated with cobalt, nickel, zinc and copper. The precursors produced in this study, 1-(2- bromoethoxy)-3-pentadecylbenzene (compound 1), 4-[2-(3-pentadecylphenoxy)ethoxy] benzaldehyde (compound 2) e 4-(3-pentadecylphenoxy)phthalonitrile (compound 3), were purified by two different procedures: column chromatography (a) and recrystallization (b). Whereas for the last, a significant reduction in the generation of residues were observed, when comparing the chromatography, which on average, 200 g of silica gel and 1650 mL of solvent were used. The liquid crystalline properties of the macromolecules were measured by means of images obtained in polarized optical microscopy (POM), during heating and cooling cycles. These images show that only free phthalocyanine 2(3),9(10),16(17),23(24)-tetrakis(-3- pentadecylphenoxy) self-organizes, displaying focal conic textures, which were observed in liquid crystal phases. Another compound that showed evidence of an organized phase was the cobalt 2(3),9(10),16(17),23(24)-tetrakis(-3-pentadecylphenoxy) phthalocyanine. However, the results of X-rays diffraction analysis suggest that only the free phthalocyanine showed the formation of a liquid crystalline phase with discotic hexagonal columnar structure (Colh).